Alpiniae oxyphyllae Fructus ameliorates renal lipid accumulation in diabetic kidney disease via activating PPARα - Zi-Jie Yan; Lin Zhang; Xin-Yao Han; Yu Kang; Shu-Man Liu; Tian-Peng Ma; Man Xiao; Yi-Qiang Xie (Asian Pacific Journal of Tropical Biomedicine)
Objective: To investigate the effects of Alpiniae oxyphyllae Fructus (AOF) on renal lipid deposition in diabetic kidney disease (DKD) and elucidate its molecular mechanisms. Methods: The mechanism of AOF in treating DKD was explored by network pharmacological enrichment analysis, molecular docking, and molecular dynamics simulation. The effects of AOF on renal function and lipid deposition were assessed in a mouse model of DKD and high glucose-stressed HK-2 cells. Cell viability and lipid accumulation were detected by CCK8 and oil red O staining. The expressions of PPARα and fatty acid oxidation-related genes (ACOX1 and CPT1A) were detected by quantitative RT-PCR, Western blot, and immunofluorescence. Furthermore, PPARα knockdown was performed to examine the molecular mechanism of AOF in treating DKD. Results: Network pharmacological enrichment analysis, molecular docking, and molecular dynamics simulation showed that the active compounds in AOF targeted PPARα and thus transcriptionally regulated ACOX1 and CPT1A. AOF lowered blood glucose, improved dyslipidemia, and attenuated renal injury in DKD mice. AOF-containing serum accentuated high glucose-induced decrease in cell viability and ameliorated lipid accumulation. Additionally, it significantly upregulated the expression of PPARα, ACOX1, and CPT1A in both in vivo and in vitro experiments, which was reversed by PPARα knockdown. Conclusions: AOF may promote fatty acid oxidation via PPARα to ameliorate renal lipid deposition in DKD.